Frequency and Risk Factors of Hypoparathyroidism after Total Thyroidectomy (Medical Forum Monthly, 2022)
Objective: To identify the frequency and risk factors of post-surgical hypoparathyroidism after total thyroidectomy.Study Design: Randomized clinical studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, Jinnah Postgraduate Medical Centre Karachi from January 2020 to January 2021 for a period of one-year.Materials and Methods: One hundred and sixty eight patients planned for total thyroidectomy were included. Frequency of hypoparathyroidism was noted at 6 months’ follow-up. Risk factors of hypo-parathyroidism were determined by applying logistic regression.Results: Transient hypoparathyroidism was seen more in carcinoma, thyroiditis and parathyroid disease patients, 44 (93.6%), 10 (21.2%) and 9 (19.1%) versus 94 (77.2%), 73 (60.2%) and 14 (11.57%, p-values 0.03, 0.048, and 0.001 respectively). Transient hypoparathyroidism seen more in lateral lymph node dissection patients including both central lymph node dissection and modified radical neck dissection, p= 0.002 and 0.03 respectively. Female gender was highly correlative with hypoparathyroidism with odds ratio OR= 2.246 (1.282–3.120, p=0.001), pathological condition of parathyroid gland OR= 1.620 (1.087–2.046, p=0.029) and extent of central lymph node dissection (bilateral) OR= 1.637 (0.081-2.231, p=0.018).Conclusion: The independent risk factors for hypoparathyroidism after total thyroidectomy are; female gender, bilateral central lymph node dissection and extent of central lymph node dissection, pre-operative parathyroid gland pathology and malignancy.